1985
DOI: 10.1007/bf01210932
|View full text |Cite
|
Sign up to set email alerts
|

Light-illumination effects on the cellular concentration of photolyase molecules in yeast

Abstract: The effects of light-illumination in the absence or presence of cycloheximide (CHX) on the number of photoreactivating enzyme molecules per haploid cell of Saccharomyces cerevisiae (NPRE) were investigated. NPRE increased, when the cells were held in buffer in light in the absence of CHX for 24 or 48 h before UV-irradiation (buffer-holding). The increase of NPRE was clearly observed in cells, whose NPRE before bufferholding was small, that is, in stationary growth phase cells grown at 37 degrees C and in logar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Moreover, our estimate for the abundance of the yeast binding factor agrees with previous estimates for yeast photolyase (11). However, it is possible that either of the two protein-DNA complexes observed in the gel assay might contain other proteins in tight association with photolyase.…”
Section: Resultssupporting
confidence: 81%
“…Moreover, our estimate for the abundance of the yeast binding factor agrees with previous estimates for yeast photolyase (11). However, it is possible that either of the two protein-DNA complexes observed in the gel assay might contain other proteins in tight association with photolyase.…”
Section: Resultssupporting
confidence: 81%
“…Another possibility is that the different rates of photoreactivation at, a,, a, may be attributed to the presence of three different types of DNA photolyase molecules, as already suggested for XS774-6A cells by Fukui and Laskowski (1985). Our results indicate that all three photolyase types are active at 23°C and that two types are active at 37"C, whereas Fukui and Laskowski (1985) have suggested that only one type is normally active. Our inferences about the number of types of photolyase molecule are drawn, however, from the presence of different photoreactivation rates, rather than from changes in the inferred numbers of photolyase molecules per cell under different treatments.…”
Section: Discussionsupporting
confidence: 69%
“…From this the number of P R E molecules per cell is determined. From changes brought about in the cellular concentration of PRE molecules by growth of the cells at different temperatures, with or without illumination during growth, by holding cells in buffer with or without illumination, and with or without cycloheximide present, Fukui and Laskowski (1985) concluded that yeast cells may contain three classes of PRE molecules. One class (PRE,) is normally active.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription of the gene for CPD photolyase is strongly regulated by environmental factors in many species (20)(21)(22)(23). The gene for photolyase in fish cells is induced by fluorescent light and by hydrogen peroxide (15,24).…”
Section: Discussionmentioning
confidence: 99%